Protest against child exploitation reflected In charles dickens' oliver twist (1838) : A sociological approach - Wulandari, Tunjung, Dr. M. Thoyibi, M.S, Nur Hidayat, M.Pd (2014)
This study is about protest against child exploitation. The problem of this study is how protest against child exploitation is reflected in Charles Dickens' Oliver Twist. The object of the study is Oliver Twist novel by Charles Dickens. It used sociological approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is Oliver Twist novel and the secondary data source is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusion. Based on the analysis it is clear that there is a close relation between structural analysis of this novel and social reality in England in early nineteenth century. Charles Dickens wants to show the protest against child exploitation in England in the early nineteenth century through Oliver Twist novel.